Designing with models : a studio guide to architectural process models - Mills, Criss (Hoboken, N.J. : Wiley, 2011)
This text focuses on the design model as an agent in the design process and outlines a variety of materials, tools and techniques used to construct models. It contains photographs illustrating the techniques used to create architectural models
Ch. 1. Model Types : Typical model types employed in the design process -- Model types -- Ch. 2. Exploration : A framework for conceiving and using models in the design process : An overview of section concepts -- Scale -- Ideas -- Alternatives -- Site models -- Manipulation -- Development -- Ch. 3. Project Development : Academic Examples in Support of Exploration : Focusing -- College complex -- Courthouse -- Chapel addition -- BiblioTierra Library -- Observatory -- Piranesi's Labyrinth Museum -- Southern Culture Complex -- Design/build project -- Urban museum/plaza -- Ch. 4. Project Development in Practice : Design Firm Examples in Support of Exploration : Mack Scogin Merrill Elam Architects (Formerly Scogin Elam and Bray) -- Callas, Shortridge Associates -- Roto Architects Inc. -- Enric Miralles and Benedetta Tagliabue Architects (EMBT Architects) -- 3XN -- BIG Bjarke Ingels Group -- Henning Larsen Architects -- Ch. 5. Rapid Prototyping : Using Digital Information to Produce Physical Models : Computer modeling -- Digitizing -- Rapid prototyping -- 3D printers -- 3D printer examples -- Laser cutting -- CNC milling -- computer numerically controlled cutting -- Ch. 6. Digital Practice : Combining Digital and Physical Model Information in Professional Practice : Morphosis -- Mack Scogin Merrill Elam Architects -- Eisenman Architects -- Gehry Partners, LLP -- Garofalo Architects -- Antoine Predock -- Coop Himmelb(l)au -- Ch. 7. Basic Assemblage : Basic Techniques for Assembling Model Components : Cutting materials -- Attaching parts -- Fitting components -- Templating -- Finishes -- Site work -- Ch. 8. Advanced Assemblage: Advanced Techniques for Form Making: Found objects -- Planar forms -- Transparent forms -- Covering frames -- Interior skeletal frames -- Transparent plastic -- Curvilinear solids -- Cut and carved forms -- Cutting and carving wood -- Building with plaster and anchoring cement -- Building with plaster -- Covering styrofoam -- Coating chipboard -- Molding with plaster and resins -- Basic casting -- Casting molds -- Malleable materials -- Ch. 9. Assemblage Case Studies: Step-by-Step Case Studies of Assembly Techniques : Case Study A Residence -- Case Study B Sculpture Foundry -- Case Study C Office Building -- Ch. 10. Tools -- Equipment and Materials : Equipment -- Materials
Includes bibliographical references and index
Keywords: Architectural models -- Handbooks, manuals, etc